Cardiac embolism and new possibilities for prevention of thrombotic events - N. A. Shostak (Klinicist)
The paper considers the main causes of cardiac embolic events. It is emphasized that atrial fibrillation is a major risk factor for systemic embolism. Main approaches to assessing the risk of stroke/systemic embolisms and their prevention using the currently available anticoagulants are given.